Advancing the Use of Laparoscopy in Trauma: Repair of Intraperitoneal Bladder Injuries. Issue 12 (December 2019) - Arnold, Michael R.; Lu, Caroline D.; Thomas, Bradley W.; Sachdev, Gaurav; Cunningham, Kyle W.; Vaio, Raymond; Heniford, B. Todd; Sing, Ronald F.
Traumatic intraperitoneal bladder rupture (IBR) requires surgical repair. Traditionally performed via laparotomy, experience with laparoscopic bladder repair (LBR) after blunt trauma is limited. Benefits of laparoscopy include decreased length of stay (LOS), less pain, early return to work, fewer adhesions, and lower risk of incisional hernia. The aim of this series is to demonstrate the potential superiority of LBR in select trauma patients. This is a retrospective review performed of all IBR patients from 2008 to 2016. Demographics, clinical management, outcomes, and follow-up were compared between LBR and open bladder repair (OBR) patients. Twenty patients underwent OBR, and seven underwent LBR. There was no significant difference in gender, age, or Injury Severity Score. There were no deaths or reoperations in either group. Average hospital length of stay and ICU days were similar between groups. There was one patient with UTI and one with readmission in each group. There were two incisional hernias and two bowel obstructions in the OBR group, with one patient requiring operative intervention. No such complications occurred in the LBR group. LBR for traumatic IBR can be safely performed in select patients, even in those with multiple extra-abdominal injuries.